Sosialisasi Pentingnya Mengetahui dan Identifikasi Bahan Tambah Pangan (Kimia) pada Makanan - Untari, Untari; Permata, Reni; Hukom, Evi Hudriyah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
Food Additives (FA) are ingredients/mixtures which are not naturally part of food raw materials, but are added to food with the aim of influencing the nature or shape of the food. Food additives are usually widely used by food industry companies as ingredients that can produce food structures that attract the attention of consumers and obtain large profits with the smallest capital. Lack of public knowledge about the dangers and how to identify Food Additives (FA) is one of the factors that many people continue to consume without thinking about the impacts that occur. The long-term impact of consuming Food Additives (FA) is the emergence of various diseases such as cancer, tumors, kidney disease, sore throat and others. This is especially true for elementary school children who really like to consume sweet, colorful, tasteful and eye-catching foods that are sold freely around their school environment. The aim of this community service is to become a means to share information on chemical food additives and simple ways to detect these food additives. From the results of the socialization, elementary school children were taught how to identify foods that contain borax in a very simple and very easy way to do so that it can be the first step in protecting themselves from consuming foods that contain dangerous food additives.